2009
DOI: 10.1158/0008-5472.can-08-0587
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functions of Transmembrane Mucin MUC13 in Ovarian Cancer

Abstract: MUC13, a transmembrane mucin, is normally expressed in gastrointestinal and airway epithelium. Its aberrant expression has been correlated with gastric colon and cancer. However, the expression and functions of MUC13 in ovarian cancer are unknown. In the present study, the expression profile and functions of MUC13 were analyzed to elucidate its potential role in ovarian cancer diagnosis and pathogenesis. A recently generated monoclonal antibody (clone PPZ0020) was used to determine the expression profile of MU… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 37 publications
8
121
1
Order By: Relevance
“…Two types of PAKs have significant differences in the structure and function. The PAK1 gene is localized within the 11q13 region, and 11q13.5-q14 amplifications involving the PAK1 locus are found in the bladder [11], ovary [12], and breast [13] cancer. Several reports have addressed the clinical correlation between PAK1 overexpression and metastasis, invasion, or progression of cancers [14e18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of PAKs have significant differences in the structure and function. The PAK1 gene is localized within the 11q13 region, and 11q13.5-q14 amplifications involving the PAK1 locus are found in the bladder [11], ovary [12], and breast [13] cancer. Several reports have addressed the clinical correlation between PAK1 overexpression and metastasis, invasion, or progression of cancers [14e18].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have addressed the clinical correlation between PAK1 overexpression and metastasis, invasion, or progression of cancers [14e18]. Julia et al [7] reported that PAK1 was increased in colorectal cancer and associated with progression and metastasis; Siu et al [12] reported that PAK1 and PAK2 play important roles in carcinogenesis and may be potential prognostic markers in ovarian cancer. In addition, PAK1 overexpression seemed to be associated with metastasis of gastric cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality rate associated with this disease may be attributable to its late diagnosis and the complications that arise from metastasis (19). Unlike most carcinomas that rely on the vasculature for metastasis, an early event in ovarian cancer dissemination is the shedding of cells from the primary tumor into the peritoneal cavity followed by diffuse "seeding" of the peritoneal cavity (20). This unique metastatic mechanism presents a distinct set of therapeutic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the functions of MUC13 other that its involvement in barrier functions of epithelium. Abnormal expression of MUC13 has been linked to gastric, colon, and ovarian cancer, as well as ulcerative colitis [28][29][30]. Further investigation on the functions and expression of MUC13 during fetal development will allow us to understand its potential involvement in DS pathogenesis.…”
Section: Time (Min)mentioning
confidence: 99%